Congo 1965-1999 Les espoirs déçus du « Brésil africain » - Maton, Joseph (OECD Development Centre Working Papers, 2001)
The economy of the Democratic Republic of Congo is now poorer than it was at independence. From the 1970s, the breakdown of supply and almost continuous erosion of demand gave way to a negative spiral leading to the informalisation, even criminalisation, of whole sectors until the country entered a war economy at the end of the 1990s. The prime reason for such a state of affairs was the atrocious governance record of the Mobutu and Laurent Désiré Kabila régimes - respectively supported, then abandoned by the Great Powers during the Cold War and manipulated by powerful regional neighbours. The resulting human catastrophe represents, apart from an appalling drama, a particularly heavy legacy for the future development of the Congo and creates the conditions for long and drawn-out destabilisation. An end to the war, conditioned on the eradication of its underlying economic causes, will provide an opportunity for a concerted strategy between the governments of the region, donors and the ...